Restrictions of establishing social bonds among the children deprived from parental care (on the case of children sheltered at the crisis centre) - Karapetyan, Tatevik (Journal of Sociology: Bulletin of Yerevan University, 2021)
The article reflects the circumstances accompanying the process of child deprivation from parental care, which limits or restricts the formation of stable and fundamental social bonds. Particularly, the article illustrates the findings of the study among 29 children deprived of parental care, who were sheltered at the Crisis Center for the period of 2019-2021. The findings of the study are interpreted in the context of social relations by T. Parsons, T. Hirschi, and J. Chris. The study showed that positions, approaches, and aspirations of establishing and maintaining social bonds by children are conditioned due to: 1) the child deprivation from parental care; 2) the nature of the action of becoming deprived of care, 3) decision making on child’s placement. The study also tackles the impacts of other accompanying circumstances within the discussed context.
Keywords: social bonds; attachment; deprivation of parental care; abandonment; social relations